The Effect of Cultural Value and Religiosity as a Moderator Variable on Anxiety about Aging of Toraja Community - Lusy Asa Akhrani; Grace Eka (Universitas Ahmad Dahlan, 2019)
AbstractÂ This research aims to determine the relationship between the cultural value of AAS (Anxiety about Aging) and religiosity as a moderator variable. The subjects of this research were Toraja community in the middle age group (40-60 years old) and late adults (60 years old and over) who were still performing the ritual of Ma 'Nene' or Ma 'Ta' Da' amounted to 174 research subjects. The instrument used in this research was INDVALS scale (Sihombing, 2014) to measure cultural value (Î± = 0.866), AAS scale (Lasher and Faulkender, 1993) to measure anxiety about aging (Î± = 0.82), and the Religiosity Scale that has been modified and rearranged based on the dimensions of religiosity by Stark & Glock (1968). The method of analysis used was PROCESS method by Andrew F. Hayes, which was used through the SPSS 21.0 for Windows statistical program. The analysis results showed that the significance value (Ï) was 0.5687>Î± = 0.05, so the research resulted that religiosity has no effect on the relationship of the variable of cultural value and anxiety about the aging of Toraja community. In addition, the cultural value of the Toraja community was confirmed to play a role in anxiety about aging by 33.7%.Â Keywords: Cultural Value, Anxiety about Aging, Religiosity, Toraja Culture.